Descriptions of three new species of Rivula Guenée [1845]1844 (Lepidoptera, Erebidae, Rivulinae) from China, with the checklist of Chinese species - Jin, Yuan Yuan; Han, Hui Lin (Zootaxa, 2025)
Three new species of Rivula Guenée (Lepidoptera, Erebidae, Rivulinae), R. medogensis sp. nov., R. puerensis sp. nov. and R. guidiana sp. nov., are described from China. The new species are illustrated with images of the adults and genitalia and compared with related species. A checklist of all species in China is provided.